Inventory monitoring web portal development using low code programming - Tan, Rui Zheng (2024)

(untitled)
This project is about developing an Inventory Monitoring Web Portal using low code programming. The programming language that was used is Node-RED language. The reason Node-RED was used is because low-code programming languages have the advantages of reduced complexity, high scalability, and rapid prototyping. In this project, the Inventory Monitoring System is a comprehensive software solution designed to streamline and optimize the management of laboratory equipment and resources. In an environment where accuracy and accountability are critical, this system encourages efficient monitoring of items to meet the needs of its users, which includes students, lab staff, and supervisors. An effective inventory monitoring system is crucial for ensuring the availability of laboratory equipment while minimizing issues such as item misplacement or mismatching. Manual tracking methods are prone to errors and can be time-consuming, leading to inefficiencies and potential equipment loss. This project addresses the need for a modern inventory monitoring system that automates and simplifies the tracking and management of lab items. The project begins with a thorough analysis of existing inventory systems, as well as research into journal articles on inventory management practices, to identify the strengths, limitations, and possible improvements for laboratory environments.